Types and Causes of Students’ Disruptive Behaviors in English Class: A Case Study at Dondaeng Secondary School, Laos - Phoumchay Vongvilay; Endang Fauziati; Koesoemo Ratih (Jurnal Penelitian Humaniora, 2021)
This study aims to explore the types and causes of students’ disruptive behaviors happen in English class. The method of this study was qualitative research. The research type was case study. The data were obtained from observation and interview. The source data were 118 students in level 3. The techniques analyzing data used three steps including data reduction, data display, and vilification. The results showed that the types of disruptive behaviors happen in the class were class disruption, aggression and goofing off. The causes of students’ disruptive behaviors were from the environment around them (friend and social life), bad learning (lazy to study and English is too difficult), and psychology needs (power, freedom, fun). Based on the correlation results, it can be inferred that the types of the disruption that happen in the English class is low behaviors. The environment has more influence for students to make the disruptive behavior in the class. Classroom management is critical in keeping students in a safe and conducive environment for effective learning. Therefore, teachers and principals should add meaning to stimulate and keep going suitable behaviors of students in classroom organizations.